2021
DOI: 10.1186/s13690-021-00704-2
|View full text |Cite
|
Sign up to set email alerts
|

One year of laboratory-based COVID-19 surveillance system in Belgium: main indicators and performance of the laboratories (March 2020–21)

Abstract: Background With the spread of coronavirus disease 2019 (COVID-19), an existing national laboratory-based surveillance system was adapted to daily monitor the epidemiological situation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the Belgium by following the number of confirmed SARS-CoV-2 infections, the number of performed tests and the positivity ratio. We present these main indicators of the surveillance over a one-year period as well as the impact of the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Data on COVID-19 incidence were collected through the national COVID-19 surveillance system, which was set up by Sciensano to monitor daily trends of virus circulation in the Belgian population [ 26 ]. Data on confirmed COVID-19 cases between 1 March 2020 and 1 June 2021 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Data on COVID-19 incidence were collected through the national COVID-19 surveillance system, which was set up by Sciensano to monitor daily trends of virus circulation in the Belgian population [ 26 ]. Data on confirmed COVID-19 cases between 1 March 2020 and 1 June 2021 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…By doing so, the laboratories were able to define thresholds for the PCR assay(s) used in their respective laboratory, to allow the reporting of SARS-CoV-2 positive test results in the four described categories without the use of a quantitative PCR assay or the need to report Ct values. Through the detailed setup of a standard curve, the correlation between RNA copies/mL present in the control material to the Ct values or equivalent metric used for their respective assay, would be defined and could later be used to report in a semi-quantitative manner to clinicians as well as to the healthdata.be platform of Sciensano, improving infection control measures [27].…”
Section: Introductionmentioning
confidence: 99%
“…At the start of the study the Alpha variant was dominant in Belgium (+—80%) and from July 2021 it was the Delta variant (+—99%) up to November 2021. Regarding the COVID-19 testing policy in Belgium, since May 2020, testing include all symptomatic individuals that fulfilled the case definition of a possible case (persons with respiratory symptoms), travellers and close contacts of positive cases [ 28 , 29 ]. However, an online survey carried out in December 2021 by Sciensano, the Belgian Institute of Public Health, showed that only 35% of participants with mild to moderate symptoms of COVID-19 reported having taken a PCR test following their symptoms [ 30 ].…”
Section: Methodsmentioning
confidence: 99%